When data are scarce, model validation should be efficient - Collins, G (Wiley, 2016)
Letter Re: Dólera-Moreno C, Palazón-Bru A, Colomina-Climent F, Gil-Guillén VF. Construction and internal validation of a new mortality risk score for patients admitted to the intensive care unit. Int J Clin Pract 2016; 10.1111/ijcp.12851. In their recent paper, Dólera-Moreno et al. describe the development of a model to predict mortality of patients admitted to ICU. However, there are design aspects in the development and validation of their model which are of concern.